Effects of different concentrations and soaking durations of Gibberellic Acid (GA₃) on seed germination and seedling growth of Hevea brasiliensis (Rubber) / Siti Nurul Aini Jokefli - Jokefli, Siti Nurul Aini (Faculty of Plantation and Agrotechnology, 2018)
The purpose of this study was to investigate the effects of different concentrations and soaking duration of Gibberellic Acid (GA₃) on rubber seed (Hevea brasiliensis). An experiment was conducted with 10 treatments and 3 replications in a Completely Randomized Design (CRD). Treatments included GA₃ with concentrations of (200, 250 and 300) mg/L in addition to a comparison with the treatment of (0 mg/L) as a control and soaking duration at (12, 24 and 36) hours. From this study, the results indicate that, there was a significant difference between concentration of Gibberellic acid (GA₃) and soaking duration on seed germination performance of rubber (Hevea brasiliensis). GA₃ 300 mg/L at 12 hours soaking (Treatment 7) gave the highest result for germination performance which is the highest mean length of plumule 23.30 cm with length of radicle 5.07 cm. The highest mean length of radicle was Treatment 8 with 6.70 cm and length of plumule 18.43 cm. However, there was no significant difference between concentration of Gibberellic acid (GA₃) and soaking duration on growth performance of rubber seedling (Hevea brasiliensis). In comparison of 12 hours, 24 hours and 36 hours soaking duration, only 12 hours soaking period gave a significant difference as compared to other treatments.